Manipulating the surface-enhanced Raman spectroscopy (SERS) activity and plasmon-driven catalytic efficiency by the control of Ag NP/graphene layers under optical excitation - Xiu Xianwu; Hou Liping; Yu Jing; Jiang Shouzhen; Li Chonghui; Zhao Xiaofei; Peng Qianqian; Qiu Si; Zhang Chao; Man Baoyuan; Li Zhen (Nanophotonics, 2021)
Highly efficient plasmon-driven catalysis and excellent surface-enhanced Raman spectroscopy (SERS) performance are proportional to the square of the local electromagnetic field (hot spot). However, a proven way to realize the enhancement in intensity and density of “hot spot” still needs to be investigated. Here, we report on multilayered Ag nanoparticle (Ag NP)/graphene coupled to an underlying Cu film system (MAgNP-CuF) which can be used as an effective SERS substrates realizing ultra-sensitive detection for toxic molecules and in situ monitoring the plasmon-driven reaction for p-nitrothiophenol (PNTP) to p,p′-dimercaptobenzene (DMAB) conversion. The mechanism of ultra-sensitive SERS response and catalytic reaction is investigated via Ag NP/graphene layer-dependent experiments combined with theoretical simulations. The research found that the intensity and density of “hot spot” can be effectively manipulated by the number of plasmonic layers, and the bottom Cu film could also reflect the scattered and excitation beam and would further enhance the Raman signals. Moreover, the MAgNP-CuF exhibits outstanding performance in stability and reproducibility. We believe that this concept of multilayered plasmonic structures would be widely used not only in the field of SERS but also in the wider research in photocatalysis.